Deuterated Arachidonic Acid Ameliorates Lipopolysaccharide-Induced Lung Damage in Mice - Alla Y. Molchanova; Svetlana N. Rjabceva; Tigran B. Melik-Kasumov; Nikolay B. Pestov; Plamena R. Angelova; Vadim V. Shmanai; Olga L. Sharko; Andrei V. Bekish; Genevieve James; Hui Gyu Park; Irina A. Udalova; J. Thomas Brenna; et al. (MDPI AG, 2022)
Arachidonic acid (ARA) is a major component of lipid bilayers as well as the key substrate for the eicosanoid cascades. ARA is readily oxidized, and its non-enzymatic and enzymatic oxidation products induce inflammatory responses in nearly all tissues, including lung tissues. Deuteration at bis-allylic positions substantially decreases the overall rate of ARA oxidation when hydrogen abstraction is an initiating event. To compare the effects of dosing of arachidonic acid (H-ARA) and its bis-allylic hexadeuterated form (D-ARA) on lungs in conventionally healthy mice and in an acute lung injury model, mice were dosed with H-ARA or D-ARA for six weeks through dietary supplementation and then challenged with intranasal lipopolysaccharide (LPS) for subsequent analysis of bronchoalveolar lavage fluid and lung tissue. Dosing on D-ARA resulted in successful incorporation of D-ARA into various tissues. D-ARA significantly reduced LPS-induced adverse effects on alveolar septal thickness and the bronchoalveolar area. Oral deuterated ARA is taken up efficiently and protects against adverse LPS-induced pathology. This suggests novel therapeutic avenues for reducing lung damage during severe infections and other pathological conditions with inflammation in the pulmonary system and other inflammatory diseases.